TIKTOK DAN AKHLAQ REMAJA : DAMPAK TIKTOK DAN SOLUSINYA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Nur Huda (Ta’dibi : Jurnal Manajemen Pendidikan Islam, 2023)
The rise of the development of information technology always brings positive and negative impacts, including TikTok. Tiktok is able to shift youtube and instagram. Tiktok with its features and artificial intelligence is able to spoil creators and viewers. The ease in how to operate TikTok and simple with attractive visual and audio displays and audio makes all people sucked in TikTok leaving other social media. TikTok content brings both positive and negative impacts. The negative impact is mostly due to content from TikTok that displays things that damage moral values, encourage criminality and endanger one's safety. Another negative impact is the effect of tiktok addiction so that sulut left the gadget because of tiktok. The next effect is on changes in behavior, lifestyle and social life. These negative impacts need to be anticipated so that they are not prolonged. Islam provides solutions to be wise in responding to the existence of TikTok, without leaving the TikTok application itself. Taking advantage of tiktok and eliminating its negative impacts, so that social and ethical life is well maintained, even using tiktok for community improvement such as educational, business, and useful information functions